Effect of biofilter on the environmental parameters and growth of goldfish (Carassius auratus) - Ahilan, B; Jayaseelan, M J Prince (Indian Journal of Fisheries, 2011)
The investigation was aimed at determining the effect of biofilter on theenvironmental parameters and growth of goldfish. The goldfish were reared in the flowthrough circular cement cisterns connected with biofilter unit andwithout biofilter. The important environmental parameters were estimatedfor a period of two months. The water pH and DO levels showed diurnalvariation. The mean gross fish production was higher in the tank fitted withbiofilter ( 291g /5m3)than the tank without biofilter ( 260g / 5m3).